Beneficial associations of low and large doses of leisure time physical activity with all-cause, cardiovascular disease and cancer mortality: a national cohort study of 88, 140 US adults. Issue 22 (November 2019) - Zhao, Min; Veeranki, Sreenivas P; Li, Shengxu; Steffen, Lyn M; Xi, Bo
Abstract : Background: Evidence on the role of very low or very high volumes of leisure time physical activity (PA) on the risk of all-cause and cause-specific mortality is limited. We aimed to examine the associations of different levels of leisure time PA with the risk of all-cause, cardiovascular disease (CVD) and cancer-specific mortality. Methods: Data were from 12 waves of the National Health Interview Surveys (1997–2008) linked to the National Death Index records through 31 December 2011. A total of 88 140 eligible participants aged 40–85 years were included. Results: Compared with inactive individuals, those performing 10–59 min/week of PA had 18% lower risk of all-cause mortality (hazard ratio (HR): 0.82, 95% confidence interval (CI): 0.72–0.95). Those who reported 1–2 times (150–299 min/week) the recommended level of leisure time PA had 31% (HR: 0.69, 95%CI: 0.63–0.75) reduced risk of all-cause mortality. Importantly, the continued benefits were observed among those performing leisure time PA 10 or more times (≥1500 min/week) the recommended minimum level (HR: 0.54, 95% CI: 0.45–0.64). For 10–59, 150–299 and ≥1500 min/week of PA, the corresponding HRs (95% CIs) for CVD-specific mortality were 0.88 (0.67–1.17), 0.63 (0.52–0.78) and 0.67 (0.45–0.99), respectively: for cancer-specific mortality were 0.86 (0.66–1.11), 0.76 (0.64–0.89) and 0.53 (0.39–0.73), respectively. In addition, there was a larger reduction in all-cause and cause-specific mortality for vigorous vs. moderate intensity PA. Conclusions: We found that beneficial association between leisure time PA and mortality starts from a low dose. Doing more vigorous exercise could lead to additional health benefits.